2006
DOI: 10.1038/sj.jp.7211618
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin and feeding intolerance in premature infants: a randomized trial

Abstract: Objectives: To evaluate the effectiveness of low-dose oral erythromycin to treat feeding intolerance in preterm infants.Design: This study was a prospective, double-blind, randomized, placebo-controlled trial on 60 premature infants suffering from feeding intolerance. Thirty infants were given oral erythromycin 1 mg/kg every 8 h and 30 infants were given placebo (normal saline). Randomization was stratified on enrollment according to gestational age whether >32 weeks or p32 weeks. The primary end point was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…Four clinical trials used low doses (3-15 mg/kg/day administered either orally or intravenously) [13][14][15][16] , whereas the other 3 trials used either an intermediate/ high dose tapering regimen (40 mg/kg for 2 days followed by 16 mg/kg for 5 days) [17] or high doses (50 mg/day) [18,19] . It is worth noting that all patients in the 'pilot' study by Ng et al [18] were included in the final analysis of their 'outcome' study [19] .…”
Section: Review Of Rctsmentioning
confidence: 99%
“…Four clinical trials used low doses (3-15 mg/kg/day administered either orally or intravenously) [13][14][15][16] , whereas the other 3 trials used either an intermediate/ high dose tapering regimen (40 mg/kg for 2 days followed by 16 mg/kg for 5 days) [17] or high doses (50 mg/day) [18,19] . It is worth noting that all patients in the 'pilot' study by Ng et al [18] were included in the final analysis of their 'outcome' study [19] .…”
Section: Review Of Rctsmentioning
confidence: 99%
“…Although it should be noted that in some studies, no significant difference was found between the placebo and erythromycin groups. [23][24][25] When we compared GGT level between the UDCA and erythromycin groups after treatment, GGT level was found to be A comparison of erythromycin and UDCA in premature infants T Gokmen et al significantly higher in the erythromycin group. Our findings suggest that UDCA was the most effective agent for preventing cholestasis.…”
Section: Discussionmentioning
confidence: 96%
“…2 Similarly, Aly et al found a significant benefit in preterm infants >32 weeks [10.5 (4.1) vs. 16.3 (5.7) days, respectively, with low-dose erythromycin (1 mg/ kg t.i.d) compared to placebo. 1 Furthermore, a Jakarta study found no significant difference in the use of lowdose erythromycin (3 mg/kg q.i.d.) in preterm infants compared to placebo.…”
Section: Discussionmentioning
confidence: 98%
“…The most common cause of feeding intolerance is low gut motility due to prematurity. 1,2 Prokinetics are commonly used to treat feeding intolerance in preterm infants. The most widely used prokinetics are metocloperamide, cisapride, and domperidone.…”
mentioning
confidence: 99%
See 1 more Smart Citation